Unity in diversity. The phenomenon of Latin American literature: pre-Spanish period (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to defining the role of Pre-Columbian era in the formation of the phenomenon of Latin American literature. The author states that indigenous culture of America is a culture-factor and a source of identity construction paradigm shift in the culture of South America in the Modern Time.
Keywords: culture; self-identity; mentality; literature